The correlation between antibiotic usage and antibiotic resistance: a 3-year retrospective study - Arulappen, Ann Lisa; Khan, Amer Hayat; Hasan, Syed Shahzad; Harun, Sabariah Noor; Chow, Ting Soo; Al-Rawi, Mahmood Basil A.; Syed, Wajid (Frontiers in Cellular and Infection Microbiology, 2025)
IntroductionMultidrug-resistant (MDR) microorganisms have increased all over the world, which is considered a public health threat. The emergence of MDR bacterial pathogens correlates with the increased antibiotic usage. This study aimed to determine the correlation between antibiotic usage and antibiotic resistance within 3 years.MethodThis was a retrospective cross-sectional study reviewing the positive bacterial culture results and the total antibiotic usage in six hospitals in Penang for 3 years from January 2021 to December 2023 through a convenient sampling method.ResultsEvery sample type has experienced a significant shift over the years. Most microorganisms from all samples significantly changed in distribution over time, except for Streptococcus pneumoniae, carbapenem-resistant Enterobacterales (CRE) Escherichia coli, and CRE Klebsiella pneumoniae. However, methicillin-resistant Staphylococcus aureus (MRSA), K. pneumoniae, and Pseudomonas aeruginosa showed significant changes in the number of total isolates from blood cultures only in the 3 years. In terms of prevalence, statistically significant differences were observed for most microorganisms from all samples except for S. pneumoniae, CRE E. coli, and CRE K. pneumoniae across the years. P. aeruginosa showed significant prevalence in blood culture over time. Cefoperazone/sulbactam, amoxicillin/clavulanic acid, ceftriaxone, and ceftazidime showed significant changes in susceptibility for K. pneumoniae over time. A statistically significant difference in total antibiotic usage across the 3 years was observed. Regarding the correlation between antibiotic usage and antibiotic resistance, Pearson’s correlation was 0.777 (p = 0.433), which is suggestive of a strong positive correlation between third-generation cephalosporin usage and extended-spectrum beta-lactamase (ESBL), whereas Pearson’s correlation was 0.762 (p = 0.448), which also suggests strong positive correlation between carbapenem usage and CREs.ConclusionThe correlation between the use of third-generation cephalosporins and ESBL rate, as well as the use of carbapenems and CRE rate, further suggests that controlling certain antibiotic usage could help mitigate the rise in MDR microorganisms.